1992
DOI: 10.1002/aic.690380902
|View full text |Cite
|
Sign up to set email alerts
|

The curious behavior of homogeneous azeotropic distillation—implications for entrainer selection

Abstract: (Stichlmair et al., 1989

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
136
0
2

Year Published

1993
1993
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(141 citation statements)
references
References 17 publications
3
136
0
2
Order By: Relevance
“…Theoretically, any candidate entrainer satisfying the feasibility and optimal criteria can be used, no matter whether it is a heavy, light, or intermediate entrainer. Literature studies on intermediate entrainers or light entrainers validate this assumption (Lelkes et al, 2002;Lang et al, 1999;RodriguezDonis et al, 2012;Shen, 2012;Shen and Gerbaud, 2013b;Laroche et al, 1992). Based on the calculation of the still path and possible composition profiles of the column sections, Lang et al (2000a, b) extended the feasibility of extractive distillation in a batch rectifier for the investigation of the separation of maximum azeotropes, Rodriguez-Donis et al (2009a, 2012a studied the maximum azeotropic mixture separation.…”
Section: Introductionmentioning
confidence: 99%
“…Theoretically, any candidate entrainer satisfying the feasibility and optimal criteria can be used, no matter whether it is a heavy, light, or intermediate entrainer. Literature studies on intermediate entrainers or light entrainers validate this assumption (Lelkes et al, 2002;Lang et al, 1999;RodriguezDonis et al, 2012;Shen, 2012;Shen and Gerbaud, 2013b;Laroche et al, 1992). Based on the calculation of the still path and possible composition profiles of the column sections, Lang et al (2000a, b) extended the feasibility of extractive distillation in a batch rectifier for the investigation of the separation of maximum azeotropes, Rodriguez-Donis et al (2009a, 2012a studied the maximum azeotropic mixture separation.…”
Section: Introductionmentioning
confidence: 99%
“…After studying more than 400 couples of azeotrope -entrainer systems, Laroche et al (1992) concluded that: (1) light entrainers, even though rare in industrial practice, could be as common as heavy entrainers theoretically since it is as easy to find a potential light entrainer as a heavy one; (2) light entrainers often represent the only viable alternative when a heavy entrainer cannot be used; and (3) light entrainers can perform as well or better than heavy entrainers.…”
Section: State Of the Art With Light Entrainermentioning
confidence: 99%
“…Figure 6(a) shows that, as the distance between the two feed stages increases, the purity of the distillate decreases; furthermore, it shows that the best separation between stages is one, but also that the best thing to do is to refrain from performing the flow split, since this will cause a decrease in the purity of ethanol being produced. The theory indicates that the distance between the two feed stages must be as large as possible, so that the solvent is present throughout most of the column at the concentration to break the azeotrope (Laroche et al, 1992;Knapp et al, 1994). But also a rectifying section is required in order to obtain ethanol, so it is not recommended to set the feed at the top (Rodriguez-Donis et al, 2009).…”
Section: Effect Of the Separating Agent Feed Stage And Flow Splitmentioning
confidence: 99%